2016
DOI: 10.1080/21505594.2016.1139279
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream infections after solid-organ transplantation

Abstract: Solid-organ transplantation (SOT) has become the preferred strategy to treat a number of end-stage organ disease, because a continuous improvement in survival and quality of life. While preventive strategies has decreased the risk for classical opportunistic infections (such as viral, fungal and parasite infections), bacterial infections, and particularly bloodstream infections (BSIs) remain the most common and life-threatening complications in SOT recipients. The source of BSI after transplant depends on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
100
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 98 publications
(130 reference statements)
8
100
2
4
Order By: Relevance
“…The trend was higher in later studies, though our study (2009‐2016) showed less frequent ESBL‐producing E. coli (12.7%) and Klebsiella (29.2%) than reported in the Greek experience (2010‐2013): 2/6 (33.3%) for E. coli and 2/5 (40%) for Klebsiella . These findings signify the increasing risk for RTR to develop infection by multidrug‐resistant pathogens …”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The trend was higher in later studies, though our study (2009‐2016) showed less frequent ESBL‐producing E. coli (12.7%) and Klebsiella (29.2%) than reported in the Greek experience (2010‐2013): 2/6 (33.3%) for E. coli and 2/5 (40%) for Klebsiella . These findings signify the increasing risk for RTR to develop infection by multidrug‐resistant pathogens …”
Section: Discussioncontrasting
confidence: 50%
“…Our data confirm that amoxicillin‐clavulanic acid and ciprofloxacin are not appropriate choices in BSI of urinary origin. The high rate of cotrimoxazole resistance may reflect its use in prophylaxis against Pneumocystis pneumonia and UTIs in the early post‐transplant period …”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic and molecular characterization of the clinical isolates revealed that 22 (73.33%) were ESBL producers, i.e. : K. pneumoniae (14), P. aeruginosa (4), M. morganii (2), E. coli (1) and E. tarda (1). The findings of our study are in accordance with several other studies that are describing an elevated frequency of ESBL infections among RTRs that received prophylactic antibiotic treatment [20,21,4,22,23].…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, the widespread use of antibiotics employed for prophylaxis and treatment of transplant recipients is leading to an increasing resistance to antibiotics among uropathogenic isolates [1,2]. Different studies reported that infections caused by beta-lactam resistant-K. pneumoniae in kidney transplant recipients were associated with higher mortality [3], recurrent UTIs being also reported [4,5].…”
Section: Introductionmentioning
confidence: 94%
“…Solid-organ transplant (SOT) recipients have a higher risk of developing infectious and noninfectious pulmonary diseases due to their immunocom promised state. 1 The incidence of pulmonary infections is, however, decreasing owing to the use of prophylactic regimens and the adjustment of immunosuppressive medications; however, pulmo nary infections remain largely responsible for mortality and morbidity among SOT recipients. 2 In this study, we analyzed the incidence of pulmonary disorders in SOT recipients and outcomes in these patients.…”
Section: Introductionmentioning
confidence: 99%